The interaction effect of trust towards profit and loss sharing element in Musharakah financing for SMES - Abdul Razak, Dzuljastri; Abd. Rahman, Nur Hasnida (Center of Islamic Finance, COMSATS Institute of Information Technology, 2017)
An Islamic equity financing, namely Musharakah financing, which operates based on profit and loss sharing (PLS) principle seems to be idle in the Islamic banking operations. Even though Islamic banks was founded based on the idea of equity financing or PLS, in reality, its application in Islamic banking operations is very minimal as the current operations of Islamic bank are dominated by the debt based financing system. This gives difficulties to a certain market segment of borrowers, especially small and medium enterprises (SMEs) in getting access to financing due to their difficulties in fulfilling debt financing requirement, mainly in providing collateral and high interest payment. Despite the resilience of Musharakah financing in the financial market, many past studies put emphasis on the need to utilize Musharakah financing for the development of SMEs. This study therefore, aims to examine the potential of Musharakah as an alternative financing for SMEs. To fulfill this objective, the main attributes of Musharakah financing, namely profit and lost sharing together with its moderating factor, namely trust were examined and tested among SMEs in Malaysia. Using survey by way of a questionnaire, this study found that the main attributes in Musharakah financing have potential in providing SMEs with greater access to financing. Furthermore, the moderating factors also play a significant role in strengthening the impact of PLS in Musharakah financing towards SMEs access to financing. The results demonstrate the viability of Musharakah financing as an alternative financing for SMEs which need crucial attention from the Islamic banks.